The Effectiveness of Parent Management Training on Oppositional Behaviors, Parenting Stress, and Parent–Child Interaction in Children With ADHD - Aghaziarati, Ali; Rahimi, Hasan (Quality of Life and Health Sciences, 2026)
Objective: This study aimed to examine the effectiveness of Parent Management Training on oppositional behaviors, parenting stress, and parent–child interaction in children with attention-deficit/hyperactivity disorder. Methods and Materials: This quasi-experimental study was conducted using a pre-test, post-test, and follow-up design with an experimental group and a control group. The statistical population consisted of children with ADHD and their parents in Tehran, Iran. A total of 30 parent–child dyads were selected through purposive sampling and randomly assigned to the experimental group and control group, with 15 dyads in each group. The experimental group received Parent Management Training in 10 weekly sessions, each lasting approximately 90 minutes, while the control group remained on the waiting list and received no structured intervention during the study period. Data were collected using standardized measures of oppositional behaviors, parenting stress, and parent–child interaction at three stages: pre-test, post-test, and follow-up. The data were analyzed using repeated-measures analysis of variance and Bonferroni post hoc tests. Findings: The results showed significant time, group, and time × group interaction effects for all study variables. The interaction effect of time and group was significant for oppositional behaviors (F = 47.29, p < .001, η² = .628), parenting stress (F = 36.21, p < .001, η² = .564), and parent–child interaction (F = 34.56, p < .001, η² = .552). Bonferroni comparisons indicated that oppositional behaviors and parenting stress decreased significantly from pre-test to post-test and from pre-test to follow-up in the experimental group, while parent–child interaction increased significantly across the same stages. No significant differences were observed between post-test and follow-up scores, indicating stability of intervention effects. Conclusion: Parent Management Training was effective in reducing oppositional behaviors and parenting stress and improving parent–child interaction in children with ADHD, and its effects remained stable during the follow-up period.